Participant characteristics associated with the effects of a physical and cognitive training program on executive functions - Tirkkonen, Anna; Törmäkangas, Timo; Kulmala, Jenni; Hänninen, Tuomo; Neely, Anna Stigsdotter; Sipilä, Sarianna (Frontiers in Aging Neuroscience, 2022)
Background Physical and cognitive interventions have been shown to induce positive effects on older adults’ executive functioning. However, since participants with different background characteristics may respond differently to such interventions, we investigated whether training effects on executive functions were associated with sex, training compliance, and age. We also investigated if change in global cognition was associated with physical and cognitive training intervention-induced changes in executive functions. Methods Exploratory data from a randomized controlled trial were analyzed. Participants were 70–85-year-old men and women who received a 12-month physical (PT) or physical and cognitive training (PTCT) intervention. Measurements of executive functions related to inhibition (Stroop), set shifting (Trail Making Test B) and updating (Verbal Fluency) were performed at baseline and 12 months. Data were analyzed using a longitudinal linear path model for the two measurements occasion. Results Stroop improved significantly more in women and participants in the low compliance subgroup who received PTCT than in counterparts in the PT subgroup (difference –8.758, p = 0.001 and difference –8.405, p = 0.010, respectively). In addition, TMT B improved after the intervention in the low compliance PTCT subgroup and worsened in the corresponding PT subgroup (difference –15.034, p = 0.032). No other significant associations were observed. Conclusion Executive functions in women and in the participants, who only occasionally engaged in training showed greater improvement after the PTCT than PT intervention. However, the additional extra benefit gained from the PTCT intervention was uniquely expressed in each executive function measured in this study.